Integration of Literature Learning and Technology Through the Creation of Student Poetry Podcasts - Iis Aprinawati; Nurmalina (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
The development of digital technology has created new opportunities for literature learning in higher education, particularly in enhancing students’ creativity and literary appreciation skills. This study aims to describe the integration of literature learning and technology through the creation of poetry podcasts as a medium for expression and literary appreciation. The research employed a qualitative descriptive approach involving students from the Indonesian Language Education study program. Data were collected through observation, interviews, and documentation of students’ podcast projects. The findings indicate that producing poetry podcasts increases students’ interest in reading literary works, deepens their understanding of poetic aesthetics, and improves their speaking and creative thinking skills. The integration of technology in literature learning has proven effective in fostering contextual, interactive, and digitally relevant learning experiences.